Perubahan Beberapa Sifat Fisika dan Kimia Gambut Jambo Aye - Aceh Utara Akibat Perlakuan Berbagai Kedalaman Drainase - Hairul Basri; M. Rusli Alibasyah; Lilis Indriansyah (Fakultas Pertanian, Universitas Syiah Kuala, 2006)
Change of Some Phisycial and Chemical Properties of Peat Soil of Jambo Aye- Aceh Utara and due to Depths of Dranage TreatmentABSTRACT. The objective of this research was to evaluate the change of physical and chemical properties of peat soil of Jambo Aye Aceh Utara due to the depth of drainage treatments. The research was set according to randomized completely design with three replication. Pipes of alluminium with length of 100 cm and diameter of 30 cm was used to set the depth of drainage treatments. The depth of drainage treatments were: no-drainage, 20 cm, 40 cm, and 60 cm. The results showed the dept of drainage on peat soil affected some of physical and chemical properties of peat soil. From the physical properties point of view, the deeper of drainage was conducted, the more subsidence occurred, otherwise the higher bulk density was occurred. From the chemical properties point of view, the drainage more than 20 cm decreased pH, N-total, P-available, K-exchangeable, and Base Saturated, otherwise increased C-organic, Cation Exchangeable Capacity, and Al-exchangeable. It was recommended to use the drainage depth of 20 cm for controlling the change of some physical and chemical properties of peat soil.